Deciphering the structural consequences of R83 and R152 methylation on DNA polymerase β using molecular modeling - Amit Srivastava; Haitham Idriss; Gobind Das; Sufian Abedrabbo; Mohd Sahir Shamsir; Dirar Homouz (PLoS ONE, 2025)
DNA polymerase β, a member of the X-family of DNA polymerases, undergoes complex regulations both in vitro and in vivo through various posttranslational modifications, including phosphorylation and methylation. The impact of these modifications varies depending on the specific amino acid undergoing alterations. In vitro, methylation of DNA polymerase β with the enzyme protein arginine methyltransferase 6 (PRMT6) at R83 and R152 enhances polymerase activity by improving DNA binding and processivity. Although these studies have shown that methylation improves DNA binding, the underlying mechanism of enhancement of polymerase activity in terms of structure and dynamics remains poorly understood. To address this gap, we modeled the methylated enzyme/DNA complex and conducted a microsecond-long simulation in the presence of Mg ions. Our results revealed significant structural changes induced by methylating both R83 and R152 sites in the enzyme. Specifically, these changes caused the DNA fragment to move closer to the C- and N-subdomains, forming additional hydrogen bonds. Furthermore, the cross-correlation map demonstrated that methylation enhanced long-range correlations within the domains/subdomains of DNA polymerase β, along with an increase in the linear mutual information value between the domains/subdomains and DNA fragments. The graph connectivity network also illustrated that methylation modulates the information pathway and identifies residues exhibiting long-distance coupling with the methylated sites. Our results provide an atomic-level understanding of the structural transition induced by methylation, shedding light on the mechanisms underlying the methylation-induced enhancement of activity in DNA polymerase β.